Leptin as a predictor of delirium in geriatric inpatients: An observational study - Yamini Ajmera; Avinash Chakrawarty; Masroor Anwar; Maroof Ahmad Khan; Prasun Chatterjee; Sharmistha Dey (Journal of the Indian Academy of Geriatrics, 2022)
Background: Delirium is a complex, reversible neuropsychiatric disorder that frequently occurs in the geriatric age group in acute care settings with multifactorial etiology and numerous knowledge gaps in the pathogenesis. Objective: This study aimed to establish an association between leptin levels and delirium in patients aged 60 years and above admitted under the geriatric medicine department of a tertiary care hospital. Materials and Methods: A prospective observational study was conducted in consecutively admitted patients to the geriatric ward. Patients were assessed for delirium within 24 h of admission and daily thereafter until they were discharged from the hospital or died using the Confusion Assessment Method (CAM) or CAM-intensive care unit with subsequent division into delirium and nondelirium groups. Serum leptin levels were measured using enzyme-linked immunosorbent assay. Results: Two hundred patients were recruited in the study. The mean age of participants was found to be 73.1 ± 8.8 years. Prevalence rates of delirium at the time of admission and incidence rates during hospital stay were found to be 20% and 5%, respectively. The occurrence of delirium was also found to be significantly associated with mortality (32.5% vs. 8.7%, P = 0.001). Serum leptin levels were found to be significantly lower in patients with delirium (2.58 ± 1.01 ng/mL vs. 10.72 ± 1.46 ng/mL, P = 0.03). Multivariable regression analysis revealed delirium to significantly correlate positively with age (Odds Ratio [OR]: 1.63 (1.07–2.47), P = 0.021) and negatively with leptin levels (OR: 0.94 (0.90–0.99), P = 0.018). Conclusion: Delirium is a frequently occurring condition in hospitalized older adults with high mortality rates. Leptin might serve as a potential predictor of delirium owing to its probable role in the pathophysiological processes of delirium.